2019
DOI: 10.1136/bmjopen-2018-028485
|View full text |Cite
|
Sign up to set email alerts
|

Association between maternal education and breast feeding practices in China: a population-based cross-sectional study

Abstract: ObjectiveTo investigate the association between maternal education and breast feeding in the Chinese population, with a consideration of household income and health-seeking behaviours.DesignA nationally representative population-based cross-sectional study.Setting77 counties from 12 geographically distinct regions in China.Participants10 408 mothers with children from 0 to 12 months of age, aged 15–53 years old (mean: 29.15, SD: 5.11) were classified into primary school or below group (n=781), middle school gr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

6
31
4
2

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 59 publications
(51 citation statements)
references
References 43 publications
6
31
4
2
Order By: Relevance
“…However, the <¥5,000 group had the second-lowest rate among the four groups, indicating that the economic advantage may not be the reason. Our results showed that women with a higher education level more readily fed the infants with milk formula, which was similar to other ndings [12,14] The women with a higher education level generally have more busy work lives and a higher family income [15] . Therefore, we also speculated that women with a high monthly family income or high education level were likely to go back to work early and must take more time for their work, and this may be the reason for the lower exclusive breastfeeding rate among these women.…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…However, the <¥5,000 group had the second-lowest rate among the four groups, indicating that the economic advantage may not be the reason. Our results showed that women with a higher education level more readily fed the infants with milk formula, which was similar to other ndings [12,14] The women with a higher education level generally have more busy work lives and a higher family income [15] . Therefore, we also speculated that women with a high monthly family income or high education level were likely to go back to work early and must take more time for their work, and this may be the reason for the lower exclusive breastfeeding rate among these women.…”
Section: Discussionsupporting
confidence: 90%
“…Therefore, many of the policies formulated by our government to a certain extent play an important role in promoting breastfeeding. In our study, the rate of exclusive breastfeeding for six months reached 29.4% and was higher than that of a large national representative survey conducted by Tang Kun et.ac in 2018, with the rate of 15.4% [12] .…”
Section: Discussioncontrasting
confidence: 72%
“…Generally, mothers who had higher literacy levels were also more likely to participate in pre-pregnancy, pregnancy, and lactation period classes and had higher health literacy too. According to Tang et al, EBF rates will increase with increase in mothers' literacy, however, they stated that the positive impact of high literacy on breastfeeding is higher in families with higher incomes (24). The importance of this issue is that future plans for the promotion of EBF should pay more attention to the promotion of maternal literacy.…”
Section: Discussionmentioning
confidence: 99%
“…In high-income countries, mother's education level is positively associated with higher breastfeeding rate. 16,17,19,[21][22][23][24][25] Even for mothers with a job, breastfeeding rate is estimated to be high, because the higher the level of education, the higher the occupational status, the better the working environment and the better knowing the bene ts of breastfeeding. In middle-and low-income countries, the relationship between breastfeeding and mothers' education level varies.…”
Section: Discussionmentioning
confidence: 99%